Photothermal Nanozymatic Nanoparticles Induce Ferroptosis and Apoptosis through Tumor Microenvironment Manipulation for Cancer Therapy. Issue 41 (11th September 2022) - Yuan, Haitao; Xia, Peng; Sun, Xin; Ma, Jingbo; Xu, Xiaolong; Fu, Chunjin; Zhou, Hongchao; Guan, Yudong; Li, Zhifen; Zhao, Shanshan; Wang, Huifang; Dai, Lingyun; et al.
Abstract: It is highly desirable to design a single modality that can simultaneously trigger apoptosis and ferroptosis to efficiently eliminate tumor progression. Herein, a nanosystem based on the intrinsic properties of tumor microenvironment (TME) is designed to achieve tumor control through the simultaneous induction of ferroptosis and apoptosis. CuCP molecules are encapsulated in a liposome‐based nanosystem to assemble into biocompatible and stable CuCP nanoparticles (CuCP Lipo NPs). This nanosystem intrinsically possesses nanozymatic activity and photothermal characteristics due to the property of Cu atoms and the structure of CuCP Lipo NPs. It is demonstrated that the synergistic strategy increases the intracellular lipid‐reactive oxides species, induces the occurrence of ferroptosis and apoptosis, and completely eradicates the tumors in vivo. Proteomics analysis further discloses the key involved proteins (including Tp53, HMOX1, Ptgs2, Tfrc, Slc11a2, Mgst2, Sod1, and several GST family members) and pathways (including apoptosis, ferroptosis, and ROS synthesis). Conclusively, this work develops a strategy based on one nanosystem to synergistically induce ferroptosis and apoptosis in vivo for tumor suppression, which holds great potential in the clinical translation for tumor therapy. Abstract : Inspired by the intrinsic properties of the tumor microenvironment to achieve tumor control through the simultaneous induction of ferroptosis and apoptosis. A nanozymatic system with phototheraml property is developed, which is mainly composed of liposomes encapsulating CuCP molecules. Proteomics analysis also further discloses the key involved proteins and pathway. The nanosystem shows great potential for translation into clinical canner therapy.